2001
DOI: 10.1016/s0020-7292(01)00581-1
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the fetal lens and orbit

Abstract: Lens and orbital measurements provide normative data for fetal growth and development. These data may be also helpful in detecting fetal ocular anomalies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
1
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 4 publications
2
31
1
4
Order By: Relevance
“…Most ultrasonographic and postmortem autopsy studies have described a linear pattern of fetal eye and eye structure growth. [5][6][7][8][9][10][11][12][13] A few authors have suggested that exponential models of growth better suit the fetal eye, including the curve model by Jeanty et al, 17 which seem to be used most by obstetricians. 16,17 Many other studies in the literature were fitted to a linear growth curve, including another fetal MR imaging study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most ultrasonographic and postmortem autopsy studies have described a linear pattern of fetal eye and eye structure growth. [5][6][7][8][9][10][11][12][13] A few authors have suggested that exponential models of growth better suit the fetal eye, including the curve model by Jeanty et al, 17 which seem to be used most by obstetricians. 16,17 Many other studies in the literature were fitted to a linear growth curve, including another fetal MR imaging study.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the literature on fetal eye growth, based on autopsy, prenatal sonography, and fetal MR imaging measurements, has suggested a linear growth curve. [5][6][7][8][9][10][11][12][13][14][15] Others have suggested an exponential growth pattern. [16][17][18] Also, Denis et al 19 in 1998 described a quadratic growth pattern on the basis of autopsy measurements.…”
mentioning
confidence: 99%
“…In the human, to evaluate the orbit or lens early in the pregnancy, it was possible to estimate not only gestational age but also fetal eye abnormalities were associated with various genetic diseases or malformations, such as Down syndrome and corpus callosum agenesis [3,4]. However, it has not been reported for the fetal orbit in goats.…”
Section: Discussionmentioning
confidence: 99%
“…The ultrasonic measurement of biparietal diameter is routinely measured during human prenatal examinations [7,21]. Recently, abdominal circumference, orbit, lens and heart were also estimated by ultrasonic scanning and relation between these and fetal growth were worked [4,11,15,21].…”
mentioning
confidence: 99%
“…The anomalies of the fetal face, including orbits, can be detected on ultrasonography (USG) (1). On USG, the orbitas appear as hypoechoic circles in the skull of fetus with the echogenic circle of the lens within it.…”
Section: Introductionmentioning
confidence: 99%